Beispiel Nr: 03
$ \text{Gegeben: } \\ P: y=a_1x^{2}+b_1x+c_1 \qquad g:y=mx+t\\ \text{Gesucht:Schnittpunkte zwischen Parabel und Gerade} \\ \text{Parabel-Gerade}\\ \textbf{Gegeben:} \\ p: y== x^2+6x+3 \qquad g: y== 4x+2 \\ \\ \textbf{Rechnung:} \\f\left(x\right)= x^2+6x+3\qquad g\left(x\right)= 4x+2\\ \bullet \text{Schnittpunkte zwischen zwei Funktionen} \\ f\left(x\right)=g\left(x\right) \\ x^2+6x+3= 4x+2 \\ x^2+6x+3-( 4x+2)=0\\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 1x^{2}+2x+1 =0 \\ x_{1/2}=\displaystyle\frac{-2 \pm\sqrt{2^{2}-4\cdot 1 \cdot 1}}{2\cdot1} \\ x_{1/2}=\displaystyle \frac{-2 \pm\sqrt{0}}{2} \\ x_{1/2}=\displaystyle \frac{-2 \pm0}{2} \\ x_{1}=\displaystyle \frac{-2 +0}{2} \qquad x_{2}=\displaystyle \frac{-2 -0}{2} \\ x_{1}=-1 \qquad x_{2}=-1 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \\ x^{2}+2x+1 =0 \\ x_{1/2}=\displaystyle -\frac{2}{2}\pm\sqrt{\left(\frac{2}{2}\right)^2- 1} \\ x_{1/2}=\displaystyle -1\pm\sqrt{0} \\ x_{1/2}=\displaystyle -1\pm0 \\ x_{1}=-1 \qquad x_{2}=-1 \end{array}\\ \end{array}\\ \\ \text{Schnittpunkt }1\\ f(-1)=-2\\ S(-1/-2)\\$